Optical approaches for neurocritical care: Toward non-invasive recording of cerebral physiology in acute brain injury - Austen T. Lefebvre; Nicole E. Steiner; Carissa L. Rodriguez; Joseph P. Angelo; Eyal Bar-Kochba; Rohan Mathur; Marek Mirski; David W. Blodgett (Neurotherapeutics)
Acute brain injury (ABI) is a complex disease process that begins with an initial insult followed by secondary injury resulting from disturbances in cerebral physiology. In the metabolically active brain, early recognition of physiologic derangements is critical in enabling clinicians with the insight to adjust therapeutic interventions and reduce risk of ischemia and permanent injury. Current established approaches for monitoring cerebral physiology include the neurologic physical examination, traditional brain imaging such as computed tomography (CT) and magnetic resonance imaging (MRI), electroencephalography (EEG), and bedside modalities such as invasive parenchymal probes and transcranial doppler ultrasound. Diffuse optical spectroscopy (DOS), diffuse correlation spectroscopy (DCS), and optical coherence tomography (OCT) are non-invasive optical techniques that have shown promise in measuring clinically relevant changes in cerebral physiology. These new modalities may offer clinicians significant benefits as they are safe, can be utilized at the point-of-care, and provide continuous measurements. This paper reviews major causes of primary and secondary ABI encountered in neurocritical care units, conventional measures of cerebral physiology during ABI, and emerging non-invasive optical techniques that have significant potential for translation to the bedside.